Solving Riddles Through Sequencing (SIRIUS): unlocking hematologic diagnoses by whole genome and transcriptome sequencing - Truger, Marietta; Meggendorfer, Manja; Walter, Wencke; Hutter, Stephan; Alsdorf, Winfried; Massenkeil, Gero; Martens, Uwe M.; Kern, Wolfgang; Hörst, Katharina; Kühn, Constanze; Reiter, Andreas; Hochhaus, Andreas; et al. (Leukemia, 2026)
In the rapidly evolving field of hematology, the diagnosis of leukemias and lymphomas poses major challenges, despite significant genetic advancements. Although established diagnostic methods comprise a multidisciplinary approach and are considered gold standard, in some cases they fall short in conclusively identifying hematological neoplasms. In this context, the current SIRIUS study (NCT05046444) delves into the potential of whole genome sequencing (WGS) and whole transcriptome sequencing (WTS) to bridge diagnostic gaps. By analyzing 106 patients with an unclear diagnosis or clinical condition following gold standard diagnostics, our study demonstrates that WGS and WTS can uncover a broader range of somatic alterations, including rare single-nucleotide variants (SNVs), small copy number variations (CNVs), and aberrant gene expression patterns not detected by conventional diagnostics. WGS and WTS provided additional diagnostic insights in 25% of cases, suggesting their value not only in enhancing diagnostic accuracy but also in contributing to more informed prognostic assessments and personalized treatment strategies. Therefore, our study underscores the importance of integrating WGS and WTS into the diagnostic toolbox for hematological neoplasms. This approach promises not only to improve patient outcomes but also to do so in a manner that is both financially sustainable and ethically sound.